2020
DOI: 10.1002/ehf2.13166
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure is independently associated with white matter lesions: insights from the population‐based LIFE‐Adult Study

Abstract: Aims White matter lesions (WML) are common structural alterations in the white matter of the brain and their prevalence increases with age. They are associated with cerebral ischaemia and cognitive dysfunction. Patients with heart failure (HF) are at risk for cognitive decline. We hypothesized that the presence and duration of HF are associated with WML. Methods and results The LIFE-Adult Study is a population-based study of 10 000 residents of Leipzig, Germany. WML were quantitated in 2490 participants who ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In HF patients, loss of GM may occur to a higher extent in the bilateral parahippocampal gyrus, bilateral cingulate gyrus, left superior temporal gyrus, and middle gyrus ( 98 ). Total WM injury is increased with the duration of HF ( 99 ). These may have negative impacts on cognitive function in HF patients.…”
Section: Discussionmentioning
confidence: 99%
“…In HF patients, loss of GM may occur to a higher extent in the bilateral parahippocampal gyrus, bilateral cingulate gyrus, left superior temporal gyrus, and middle gyrus ( 98 ). Total WM injury is increased with the duration of HF ( 99 ). These may have negative impacts on cognitive function in HF patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the univariable analysis, the risk for advanced WMHs was 4.4-fold in participants with HF ( Table 2 ). After adjustment for age and sex, stroke (OR 2.90, 95% CI 1.52–5.56, p = 0.001), hypertension (OR 2.06, 95% CI 1.57–2.70, p<0.001), HF (OR 2.88, 95% CI 1.27–6.55, p = 0.012), and PR interval ≥160ms (OR 1.40, 95% CI 1.05–1.86, p = 0.022) were associated with increased risk of advanced WMHs [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Adverse effects of AF on cerebral small vessel disease may be one mechanism by which AF contributes to cognitive impairment. However, several studies failed to demonstrate an association between AF and WMHs [ 28 , 47 , 48 ]. Of note, a cross-sectional analysis of the community-based Framingham Heart Study did not report any associations between AF and lower total brain volume [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vogels et al found that patients with HF had more WMLs and lacunar infarcts compared to both healthy participants and patients with other cardiovascular diseases [ 55 ]. In addition, a recent study by Stegmann et al demonstrated an increase in WMLs with a longer HF disease duration [ 57 ]. Frey et al, however, found that the extent of WMLs in patients with HF was not increased at baseline and progressed within the limits of physiological ageing [ 19 , 50 ].…”
Section: Anatomical Brain Changesmentioning
confidence: 99%